Hygro-mechanical analysis of wood-adhesive joints. (15th August 2019) - Bachtiar, Erik V.; Konopka, Daniel; Schmidt, Benjamin; Niemz, Peter; Kaliske, Michael
Highlights: Simplified wood-adhesive joint model adapted from a cohesive element. Implementation of mechanical behaviour together with multi-Fickian moisture transport in a wooden joint. Comparison of simulation results to experimental investigations of adhesive joints. Capturing the moisture gradient around the adhesive joint. Abstract: A new numerical model for wood-adhesive joints, which allows an efficient hygro-mechanical analysis of a glued joint by means of the finite element method, is proposed. A cohesive element model is modified by adding features to simulate the mechanical behaviour of and the moisture transport in the joint. The numerical investigations of two wood species, European beech ( Fagus sylvatica L.) and Norway spruce ( Picea abies L.), are carried out based on experimental studies available in the literature. The simulated specimens contain a single bond line of animal adhesive, which is commonly found in historical wooden objects. Additionally, experimental investigations are also carried out in parallel to further validate the model. The results show that the numerical simulations are in agreement with the experimental results at mechanical loading. Under moisture loading, however, the numerical results are diverse in comparison to the experimental results. The reason for this difference is primarily due to the incomplete experimental data, which serve as input parameters for the numerical simulation.